A Stochastic Frontier Approach to Model Technical Efficiency of Rice Farmers in Bangladesh: An Empirical Analysis (The Agriculturists, 2012)
A study was conducted in the year 2008-2009 to estimate the farm-size-specific productivity and technical efficiency of all rice crops. Farm-size- specific technical efficiency scores were estimated using stochastic production frontiers. There were wide of variations of productivity among farms, where large farms exhibited the highest productivity. Gross return was the highest for small farms and net return was the highest for marginal farms. The lowest net return or the highest cost of production was accrued from both the highest wage rate and highest amount of labour used in medium farms. The marginal farms experienced the highest benefit-cost ratio (BCR) followed by small and medium farms. Average technical efficiency for large, medium, small, marginal and all farms were respectively 0.88, 0.92, 0.94, 0.75 and 0.88. There were significant technical inefficiency effects in the production of rice for marginal farms only. In this case, production cannot be increased by increasing efficiency with the existing technology except in marginal farms. The application of efficient management system would be able to increase production in the marginal farms. For other farms, increased managerial capacity is not enough for increased production, rather new investment and advanced technology are needed to increase production in these farms. On an average, farmers could increase 12 percent output with existing inputs and production technology. Fertiliser, manure, irrigation cost, insecticide cost, area under production and experience were important factors to increase production. In the technical inefficiency effect, age, education and family size had positive impact on efficiency effect, whereas land under household had negative impact on efficiency effect. DOI: http://dx.doi.org/10.3329/agric.v10i2.13132 The Agriculturists 2012; 10(2) 9-19